Excess Mortality, Institutionalization and Homelessness Among Status Indians in Canada - Randall K. Q. Akee; Donna Feir (Institute of Labor Economics (IZA), 2016)
In this paper we use confidential-use Census and administrative data to produce the first national estimates of excess mortality, institutionalization and homelessness for the largest Indigenous population in Canada from the ages of 5 to 64. We identify mortality rates at least twice the Canadian average and find exceptionally high mortality rates for young Indigenous women and girls – up to four times the Canadian average at certain ages. We show mortality rates are even higher on reserve – up to five times the Canadian average. These relative mortality rates are higher than the relative mortality rates of African Americans and the Native Americans to non-Hispanics in the United States. We also estimate very high rates of institutionalization and homelessness, especially among men and as a result there are stark gender ratio imbalances among this population. We speculate that this gender imbalance may play a role in excess female mortality in addition to several other socioeconomic factors.
Keywords: J10; J15; J16; O15; I15; I14; I32; 330; mortality; First Nations; Native American; Status Indian; homelessness; institutionalization; gender bias